FOR REVENGE: THE PHENOMENON OF EMO MUSIC PERFORMANCES AND AUDIENCE EMOTIONS - Ardini, Ni Wayan; Wijaya, I Nyoman Cahyadi; Mudana, I Gede (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
This research was conducted for the purpose of identifying the character of emo (emotional hardcore) music performances and their relationship to the emotional situation of the audience watching them, especially in the case of a music group in Indonesia named for Revenge. This qualitative research, which relies on document studies, observations and interviews, found that this underground group with an emo (emotional hardcore) character, with themes of inner conflict, suffering and rebellion, especially in matters of love, deserves to label itself as